Comprehensive investigation of performance of construction and demolition waste based wood fiber reinforced geopolymer composites - Ozcelikci, Emircan; Ozdogru, Emine; Tugluca, Merve Sonmez; Ilcan, Huseyin; Sahmaran, Mustafa (ELSEVIER, 2024)
This study focuses on developing eco-friendly building materials by valorising construction and demolition waste (CDW) in geopolymer matrices. Various CDW-based materials, including brick, tile, concrete, and glass waste, were utilized. Additionally, CDW-based waste wood fiber (WWF) was chemically treated and integrated as a reinforcing fiber. The developed CDW-based WWFreinforced geopolymer composites were extensively evaluated through workability, strength, durability, and microstructural analysis. Findings showed that incorporating 2.00 vol % and 4.00 vol % WWF in geopolymer composites resulted in a slight decrease in compressive strength, while at 6.00 vol % and 8.00 vol % WWF, significant decreases were observed. Flexural strength showed improvement up to 4.00 vol % WWF, with significant enhancement of 17.67 % compared to plain geopolymer. This enhancement was attributed to the increased adhesion capability and improved interlocking and compatibility between the geopolymer matrix and chemically treated WWF. However, the advantages of WWF addition were limited at higher usage ratios due to its higher water absorption capacity and potential agglomeration behaviour. In this context, water absorption increased with WWF, ranging from 30.87 % to 59.01 %, while improvements in freezethaw resistance were observed up to 6.00 vol % WWF usage. The microstructural analysis further corroborated these findings by confirming the presence of interlocking and agglomeration phenomena within the composites.
Keywords: Construction and demolition waste; Geopolymer; Waste wood fiber; Upcycling; Mechanical performance; Durability; CEMENT-BASED COMPOSITES; RICE HUSK ASH; MECHANICAL-PROPERTIES; FLY-ASH; WATER-ABSORPTION; GLASS-FIBERS; STRENGTH; STEEL; POLYPROPYLENE; CONCRETE; Construction & Building Technology; Engineering